2015
DOI: 10.1007/s40843-015-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments on nanomaterials-based optical sensors for Hg2+ detection

Abstract: Mercuric ion (Hg 2+ ), released from both natural and industrial sources, has severe adverse effects on human health and the environment even at very low concentrations. It is very important to develop a rapid and economical method for the detection of Hg 2+ with high sensitivity and selectivity. Nanomaterials with unique size and shape-dependent optical properties are attractive sensing materials. The application of nanomaterials to design optical sensors for Hg 2+ provides a powerful method for the trace det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 131 publications
0
30
0
Order By: Relevance
“…For a collection of other nanomaterial-based probes developed for Hg 2+ monitoring, readers are referred to the brilliant review article by Duan and Zhan (2015).…”
Section: Mercuric (Ii) (Hg 2+ ) Nanoprobesmentioning
confidence: 99%
“…For a collection of other nanomaterial-based probes developed for Hg 2+ monitoring, readers are referred to the brilliant review article by Duan and Zhan (2015).…”
Section: Mercuric (Ii) (Hg 2+ ) Nanoprobesmentioning
confidence: 99%
“…However, this review focused mainly on the determination and speciation studies of arsenic rather than mercury. Duan and Zhan [ 42 ] reviewed recent use of nanomaterials-based (noble metal nanoparticles, fluorescent metal nanoclusters, semiconductors quantum dots, and carbon nanodots) optical sensors for Hg(II) detection. They concluded that the advantages of using nanomaterials for Hg(II) detection and removal included higher sensitivity and selectivity, simpler and more rapid procedures, and lower cost than that of conventional methods.…”
Section: Reviews Of the Determination Of Mercurymentioning
confidence: 99%
“…Therefore, compared with the previous works, our paper sensor is both sensitive and accurate for the detection of Salmonella . The future of our work will focus on further improving the sensitivity of the Salmonella biosensor based on lanthanide (Ln 3+ )-doped nanoparticles [47], ZnO nanomaterials [48], and surface-enhanced Raman scattering active nanomaterials [49].…”
Section: Sensitivity and Cross-reactivity Of The Immunochromatographimentioning
confidence: 99%